The Secreted Protein Disulfide Isomerase Ag1 Lost by Ancestors of Poorly Regenerating Vertebrates Is Required for Xenopus laevis Tail Regeneration - Ivanova, Anastasiya S.; Tereshina, Maria B.; Araslanova, Karina R.; Martynova, Natalia Y.; Zaraisky, Andrey G. (Frontiers in Cell and Developmental Biology, 2021)
Warm-blooded vertebrates cannot regenerate lost limbs, whereas fishes and amphibians can. We previously hypothesized that this reduction in regenerative capability could be explained in part by the loss of some genes important for the regeneration in ancestors of warm-blooded vertebrates. One of such genes could be ag1, which encodes secreted protein disulfide isomerase of the Agr family. Ag1 is activated during limb and tail regeneration in the frog Xenopus laevis tadpoles and is absent in warm-blooded animals. The essential role of another agr family gene, agr2, in limb regeneration was demonstrated previously in newts. However, agr2, as well as the third member of agr family, agr3, are present in all vertebrates. Therefore, it is important to verify if the activity of ag1 lost by warm-blooded vertebrates is also essential for regeneration in amphibians, which could be a further argument in favor of our hypothesis. Here, we show that in the Xenopus laevis tadpoles in which the expression of ag1 or agr2 was artificially suppressed, regeneration of amputated tail tips was also significantly reduced. Importantly, overexpression of any of these agrs or treatment of tadpoles with any of their recombinant proteins resulted in the restoration of tail regeneration in the refractory period when these processes are severely inhibited in normal development. These findings demonstrate the critical roles of ag1 and agr2 in regeneration in frogs and present indirect evidence that the loss of ag1 in evolution could be one of the prerequisites for the reduction of regenerative ability in warm-blooded vertebrates.